Study of Coconut Dregs Fertilizer on the Growth and Yield of Mung Bean Plants (Vigna radiata L) - Agusthiana, Mifthaqul; Andarula Galushasti (KHD Production, 2025)
The decline in mung bean (Vigna radiata L.) production in Indonesia is partly due to the unbalanced use of inorganic fertilizers. This study aims to determine the effect of coconut pulp waste fertilizer on the growth and yield of mung bean production. The study was conducted in Kesilir Village, Wuluhan District, Jember Regency, East Java, in September–November 2024 using a non-factorial Randomized Block Design (RBD) with one treatment factor (coconut pulp fertilizer doses: 0, 100, 200, 300, 400, and 500 g/plot) and four replications. The parameters observed included plant height, number of pods, dry seed weight, and biomass. The results of the ANOVA analysis showed that coconut pulp fertilizer significantly affected the dry seed weight per sample and dry seed weight per plot. The best treatment was shown at a dose of 500 g/plot with an average dry seed weight of 27.10 g/sample and 547.5 g/plot. Coconut dregs fertilizer has the potential to be an environmentally friendly alternative fertilizer to increase green bean yields.